Risalah Darurat: Strategi Kerajaan dalam Memenangi Jiwa dan Pemikiran Orang Cina di Tanah Melayu, 1948–1960: Emergency Leaflets: The Government’s Strategy in Winning the Hearts and Minds of the Chinese in Malaya, 1948–1960 (KEMANUSIAAN The Asian Journal of Humanities, 2023)
In Malaya, the Chinese were influenced the most by the communist movement and thus developed into the largest supporting group. In this situation, the government of the Federation of Malaya (hereinafter the government) has planned and carried out various strategies to win their hearts and minds in order to thwart them from joining the communist struggle. The discussion in this article is based on Chinese-written Emergency Leaflets disseminated by the government through the Department of Information specifically for the Chinese during the emergency period (1948–1960). This study aims to discuss the importance of physical propaganda in the form of Emergency Leaflets in helping the government to rally support from the Chinese as well as to look into the government’s stands towards the communist movement. This study clearly shows that the Emergency Leaflets have been used by the government as propaganda and an instrument of communication to explain to the Chinese about the situation in Malaya including the danger of communist threats and efforts taken in the fights against the communists. Their cooperation was also called in combating the communist movement. Thus, the leaflets played an important role as a medium of propaganda for the government to restrain the communists’ influences during the emergency.Di Tanah Melayu, orang Cina merupakan golongan yang paling ramai terpengaruh dengan gerakan komunis sehingga membentuk kumpulan penyokong yang paling besar. Dalam keadaan ini, kerajaan Persekutuan Tanah Melayu (seterusnya disebut sebagai kerajaan) membuat perancangan dan menjalankan pelbagai strategi untuk memenangi jiwa dan pemikiran mereka supaya tidak menyertai perjuangan komunis. Perbincangan dalam makalah ini adalah berdasarkan penelitian terhadap Risalah Darurat (Emergency Leaflets) dalam tulisan Cina yang disebarkan oleh kerajaan melalui Jabatan Penerangan kepada penduduk Cina pada zaman darurat (1948–1960). Kajian ini bertujuan membincangkan kepentingan propaganda fizikal dalam bentuk Risalah Darurat untuk membantu kerajaan meraih sokongan daripada orang Cina selain melihat pendirian kerajaan terhadap gerakan komunis. Kajian ini dengan jelas menunjukkan Risalah Darurat digunakan oleh kerajaan sebagai propaganda dan instrumen komunikasi untuk menerangkan kepada penduduk Cina tentang situasi di Tanah Melayu termasuk bahaya ancaman komunis serta langkah yang diambil dalam memerangi komunis. Kerajaan turut menyeru penduduk Cina agar memberi kerjasama dalam menumpaskan gerakan komunis. Justeru, risalah memainkan peranan penting sebagai medium propaganda kerajaan untuk memerangi pengaruh komunis semasa darurat.